Prevention of Hypertension through Health Education for the Elderly: - Andri Kusuma Wijaya; Dewi Suliyanti; Fatsiwi Nunik Andari; Hasan Husin (Gayaku Publisher, 2024)
Hypertension is a condition characterized by high blood pressure, with systolic blood pressure levels of 140 mmHg or higher and diastolic blood pressure levels of 90 mmHg or higher. Hypertension affects people of all ages and social groups worldwide, with the number of individuals suffering from this condition continuously increasing year by year, including among the elderly. The elderly are individuals undergoing the ongoing process of aging, which is marked by a decline in the body's ability to cope with environmental stressors. This aging process represents a form of anatomical functional decline, which is, in fact, a biological phenomenon encompassing evolutionary and maturation signs that continue throughout an organism's life. One such change occurs in the vascular system, where thickening of the blood vessels in the elderly can lead to hypertension. Hypertension can be caused by several factors, including a lack of knowledge and unhealthy lifestyle habits, such as excessive salt consumption from fast food beyond normal limits. As a result, public awareness about hypertension prevention remains low.